Arabic for Understanding Qur’an: Analysis of Fehm E-Qur’an Course and Its Impact on University Students of Pakistan - Altaf Ahmed; Nasurullah Qureshi; Muzaffar Ali; Abdul Samee Jessar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research basically tries to evaluate the impact of the Fehm-ul-Qur’an courses (I II) on Arabic language acquisition among university students. The Higher Education Commission (HEC) of Pakistan has recently mandated this course for all undergraduate and graduate programs (effective Fall 2025). These courses fundamentally facilitate comprehension of the Holy Qur’an; however, they have been structured in a way that also help in foundational Arabic learning. Adopting a mixed-methods approach, the study uses quantitative method by textual analysis of the prescribed textbook Muallim Ul Qur’an. On the other hand, quantitative methods have been employed during data collection from teachers and learners to evaluate pedagogical effectiveness and learning outcomes. The textbook has been analyzed including main Course Learning Outcomes (CLOs). Course contents focus on vocabulary acquisition, direct translation skills, grammatical competence, and syntactic awareness. With that, units of the book along with activities and exercises have been discussed in detail. Findings suggest that these activities are based on active learning and support incremental language acquisition. However, there are some notable challenges including variations in student preparedness and instructional delivery besides HEIs seriousness. In the end, it offers pedagogical and curricular recommendations for further Arabic language proficiency and improvement within higher education contexts in Pakistan i.e. separate course content at each degree (BS, MS/MPhil. and PhD) level.